1993
DOI: 10.1021/bi00095a016
|View full text |Cite
|
Sign up to set email alerts
|

Actin conformation is drastically altered by direct interaction with membrane lipids: A differential scanning calorimetry study

Abstract: One of the current dogmas in cytoskeleton research holds that actin filaments are attached to the cell membrane through integral membrane actin-binding proteins. We have challenged this concept, using an in vitro system composed of pure actin and liposomes, and have found that actin may also interact with membrane lipids. Differential scanning calorimetry (DSC) shows that when the actin molecule is in contact with such lipids, it undergoes a major conformational change which results in the complete disappearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…The mechanism of actin trafficking and binding to the cell surface is not well understood. However, actin can bind to membrane lipids such as phospholipids (51)(52)(53)(54)(55), and direct interactions between actin and cell membranes are possible in vivo although actin does not have a transmembrane domain. Furthermore, studies by Hu et al (50) also showed that cellsurface actin was not derived from the serum in tissue culture experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of actin trafficking and binding to the cell surface is not well understood. However, actin can bind to membrane lipids such as phospholipids (51)(52)(53)(54)(55), and direct interactions between actin and cell membranes are possible in vivo although actin does not have a transmembrane domain. Furthermore, studies by Hu et al (50) also showed that cellsurface actin was not derived from the serum in tissue culture experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show the application of DSC for characterization of a complex of isolated myosin head, or myosin subfragment 1 (S1), with F-actin. Previously, this method was successfully used to study actin polymerization [3] and interaction of F-actin with membrane lipids [4] and with phosphate analogues [5]. The thermal unfolding and domain structure of S1 and their changes induced by nucleotide binding have also been studied by the DSC method [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In that respect, F-actin molecules display the same way as many polycations do, as has been long known (17). The presence of negatively charged lipid in the lipid mixture used seems very important for the interaction of F-actin with the lipid bilayer because F-actin cannot interact with neutral phospholipids (4,18,19). We also failed in measuring the ion conductivity of BLM made up of only neutral lipids (results not shown).…”
Section: Discussionmentioning
confidence: 94%
“…The rst is the expected electrostatic adsorption of long, brillar protein molecules on the membrane surface, a result of the polyelectrolyte nature of F-actin and the negative charge of the membrane (4,19,26). The interaction is strong enough to produce long furrows on the membrane surface just beneath the protein molecule and is visible also on the hydrophobic fracture surface of membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation